Annotated bird sighting list for Spring 1994 compiled by Peter Ernzen - Ernzen, Peteret al (1994)
An annotated list of birds sighted by Peter Ernzen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed